2016
DOI: 10.5898/jhri.5.2.yogeeswaran
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Robot Anthropomorphism and Robot Ability on Perceived Threat and Support for Robotics Research

Abstract: *indicates that both authors contributed equallyThe present research examines how a robot's physical anthropomorphism interacts with perceived ability of robots to impact the level of realistic and identity threat that people perceive from robots and how it affects their support for robotics research. Experimental data revealed that participants perceived robots to be significantly more threatening to humans after watching a video of an android that could allegedly outperform humans on various physical and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 49 publications
(51 reference statements)
1
39
0
1
Order By: Relevance
“…This may seem surprising, considering that prior work suggests that people favor anthropomorphic robots over mechanomorphic robots (Gray et al, 2007). However, prior work shows that favoring of anthropomorphic robots depend on the number of robots (Fraune et al, 2015b) and context (Kuchenbrandt et al, 2011;Sauppé and Mutlu, 2015;Yogeeswaran et al, 2016) of interaction. In the context of this study, participants competed in a game and that competitive context was critical in the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This may seem surprising, considering that prior work suggests that people favor anthropomorphic robots over mechanomorphic robots (Gray et al, 2007). However, prior work shows that favoring of anthropomorphic robots depend on the number of robots (Fraune et al, 2015b) and context (Kuchenbrandt et al, 2011;Sauppé and Mutlu, 2015;Yogeeswaran et al, 2016) of interaction. In the context of this study, participants competed in a game and that competitive context was critical in the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature emphasizes how highly human-like robots can be perceived as menacing by users, especially when they appear able to perform better than humans (Yogeeswaran et al, 2016) and display autonomy (Złotowski et al, 2017). According to the “threat to distinctiveness hypothesis” advanced by Ferrari et al (2016), the increasing blur of boundaries between robots and humans destabilizes the perception of “human uniqueness,” and tends to generate growing concern on the negative impacts of this technology (Ferrari et al, 2016).…”
Section: Social Robotics As Applied Anthropomorphismmentioning
confidence: 99%
“…Other studies have also demonstrated that robots, particularly those that look more human like, are considered a threat to identity (e.g., Ceh & Vanman, ; Kamide, Kawabe, Shigemi, & Arai, ; Strait, Aguillon, Contreras, & Garcia, ). This perceived threat to identity is particularly acute when the human‐like robot's abilities are superior to the human's (Yogeeswaran et al, ).…”
Section: Robots As a Threatmentioning
confidence: 99%